Differences in the isotopic composition of individual grains and aggregated seed samples affect interpretation of ancient plant cultivation practices - James, Nathaniel; Winter-Schuh, Christine; Kenoyer, J. Mark; D'Alpoim Guedes, Jade; Makarewicz, Cheryl A. (Frontiers in Environmental Archaeology, 2025)
The stable carbon (δ13C) and nitrogen (δ15N) isotope analysis of charred archaeological grains provides a remarkably precise scale of information: the growing conditions under which a plant was cultivated in a single field and season. Here we investigate how the measurement of single individual grains or aggregate “bulk” samples for carbon and nitrogen isotopes impacts how we characterize variation and, consequently, our interpretations of ancient cultivation practices. Using experimentally grown barley (Hordeum vulgare var. nudum), this work investigates δ13C and δ15N intra-panicle variation between both uncharred and charred individual grains from four plants. We found limited intra- and inter-panicle isotopic variation in single-grain isotope values, ca. 0.5‰ in δ13C and ca. 1‰ in δ15N, reemphasizing the degree to which grains are representative of their local growing conditions. To explore the interpretive impact of aggregate versus single-grain isotopic sampling, we measured charred barley recovered from a single storage context excavated from Trench 42 (ca. 1,900 BCE) at Harappa. Aggregate samples of a random selection of Trench 42 barley demonstrated remarkable inter-sample homogeneity, with a < 0.5‰ difference in δ13C and δ15N values, demonstrating aggregate samples capture well a representative isotopic average of a single depositional context. However, the measurement of single grains revealed moderate 2–3‰ variation in δ13C and an outstandingly wide isotopic variation of ca. 8‰ in δ15N values, indicating the degree to which growing conditions varied beyond what the isotope ratios from aggregate samples indicated. These results highlight how decisions in the selection and measurement of archaeological charred grains for isotopic analysis impact data resolution, with profound consequences for understanding past agricultural diversity.